Psychological Effects of Work: Burnout and its Consequences - Kuświk, Justyna (Studia Historiae Oeconomicae, 2012)
Job burnout is one of the consequences of work. Its appearance is conditioned by a variety of factors that are to a great extent linked with attitudes and behaviours of the workers and their way of functioning and to some extent with the culture of the surrounding people. The first part of the article provides characteristics of the phenomenon of burnout. The second part is a review of research that reveals the scope of the issue. The analysis of relationships between burnout and the predisposing and preventive factors has been omitted. The third part is devoted to an analysis of the consequences of burnout from different perspectives.